While the duke was sleeping - Parish, Samara (Parish, Samara. England's sweethearts, 2025)
"When Adelaide Rosebourne must impersonate her mistress for a few days, it doesn't seem like it'll be a difficult task, even if her mistress's supposed fiancé is in a coma. All she has to do is wait until he wakes up and then convince him to retract the proposal--thereby securing a tidy reward. What she doesn't count on is the arrival of the duke's brother and his damned inconvenient interest in her affairs. But does it really matter? She'll be gone before he finds out the truth. Rhett Montgomery knows two things--that he is woefully unprepared to take over the dukedom, and that the woman who claims to be his brother's betrothed is not who she says she is. No debutante swears so fiercely or kisses with such recklessness. Investigating is what any good brother would do, isn't it? As long as he doesn't start falling for her charms as well."--Back cover.